Agrochemical and Pesticides Safety Handbook (The) - Waxman, Michael F. (CRC Press, 2009)
Worldwide, there are a vast array of agricultural pesticides and chemicals used to eliminate pests and to protect health, food, and fiber. The safe handling, usage, and disposal of these chemicals and pesticides is of vital importance. The Agrochemical and Pesticides Safety Handbook serves as a field resource on the hazards of these pesticides and chemicals.